Capital markets financing for agricultural business development in Tanzania: A case of cocoa farming in Kyela and Rungwe districts - Godfrey Frank Molela (The Journal of Entrepreneurial Finance (JEF), 2016)
This study tries to explore the financing opportunity for smallholder cocoa farmers available at capital markets through enterprise growth market (EGM) financing window. The research findings from 122 cocoa farmers revealed that, in average a single cocoa farmer needed Tshs. 551,808.12 per acre as capital investment in a given season. At the time of data collection the cocoa prices at London and New York futures markets were Tshs. 6,266.75/Kg and Tshs. 6,148.62/Kg respectively at prevailed rates which were far above the production cost. In this case the envisaged gross margin was sufficient to service issuers' interest of running their business lucratively and collectors' interests of getting their investment needs met. The study considered the concessionary terms and conditions on EGM for small and medium enterprises (SMEs) to fit cocoa sector in the financial arrangement. Cocoa farmers could raise needed capital for cocoa businesses from the public who would later become shareholders to such businesses. With Bank of Tanzania (BOT) being the guarantor, the findings concluded that the financing arrangement was viable since the interests of issuers and collectors were protected. Capital markets financing could now become an alternative best solution for finance to smallholder farmers following poor accessibility of the same from existing sources especially financial institutions.
Keywords: 650